Thymus citriodorus: phenolic characterization and antioxidant activity - Pereira, Olívia R. (2012)
The present work aims to determine the phenolic composition of Thymus citriodorus and to estimate its antioxidant capacity. An ethanolic extract was prepared from the plant and its total phenolic and flavone contents were determined. The phenolic extract was fractionated by reversed-phase HPLC and the major phenolic compounds of each fraction were identified by ESI-MS and MSn analysis, in order to establish the specific phenolic profile of the plant. The total phenolic compounds in the ethanolic extract of Thymus citriodorus accounted for 138,75±13,56 mg/g, and its content of flavones was estimated as 27,30±2,15 mg/g. Moreover, the interpretation of the fragmentation pathways under ESI-MS/MS of the collected HPLC fractions allowed concluding that the major phenolic compounds in the plant included some glycoside derivatives of luteonin, naringenin and eriodictyol. Also, the phenolic extract showed a considerable antioxidant activity, as evaluated by the 2,2-diphenyl-1-picrylhydrazyl radical scavenging potential and the reducing potential, suggesting that Thymus citriodorus can be an important source of natural antioxidants.